PERAN EKSTRAKURIKULER DALAM MENUNJANG KEGIATAN INTRAKURIKULER BAHASA MANDARIN DI INDONESIA - Mizanurhamni, Mizanurhamni (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2019)
Today, more and more people are interested in learning Mandarin, but not all of these students have adequate facilities to learn directly into China, so the process of learning Mandarin occurs not in Chinese, imposes a process of practicing language skills and communication skills in activities intracuricular. Intracurricular activities themselves have limitations, which must be compliant with the curriculum, so that it is not flexible in terms of time, material coverage and content. The analysis in this study shows how extracurricular roles in the process of learning Chinese. By utilizing extracurricular activities as a support in the process of learning Chinese, extracurricular activities are expected to be a solution to complement the limitations of intracurricular activities.